ATO transparent conductive film and preparation method thereof
High uniform tin antimony targets are prepared by inert gas spraying method and vacuum hot pressing method, which are used to prepare ATO transparent conductive films, which solves the problems of low conductivity, density and strength of ATO films and achieves resistivity and density Significant improvement.
Patent Information
- Application Number
- CN202411821125.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
AI Technical Summary
The conductivity, density and strength of ATO films are low, and there are problems of excessive resistance and low density.
Tin antimony alloy powder was prepared by inert gas spraying method, and a high uniform tin antimony target was prepared by vacuum hot pressing method, which was used for sputtering to prepare ATO transparent conductive film.
The conductivity and density of the ATO film are significantly improved, the uniformity and density of the film are improved, and thus the resistivity is reduced.
Smart Images

Figure BDA0005183133210000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to an ATO transparent conductive film and a preparation method thereof. Background Art
[0002] In recent years, the research on transparent conductive films on flexible substrates has attracted the attention of countries around the world, because the application prospects of transparent conductive films on flexible substrates are promising. They not only have the characteristics of transparent conductive films on glass substrates, but also have many unique advantages, such as being bendable, light weight, impact resistant, easy to produce on a large scale, and easy to transport. They have broad application prospects in flexible light-emitting devices, plastic liquid crystal displays, and solar cells on plastic substrates. At present, the vast majority of transparent conductive film materials used in applications are tin-doped indium oxide (Sn-doped In2O3, referred to as ITO film). Although ITO film is currently a transparent conductive film material with excellent comprehensive optoelectronic properties and the most widely used, indium is toxic, expensive, and has poor stability. There are problems such as indium diffusion causing device performance attenuation. People are trying to find a low-cost and high-performance ITO replacement material. Among them, aluminum-doped zinc oxide (Al-dopedZnO, referred to as AZO film) and antimony-doped tin oxide (Sb-doped SnO2, referred to as ATO film) have the characteristics of cheap materials, non-toxicity, and electrical and optical properties comparable to ITO, and have become the most competitive transparent conductive film materials. However, AZO (antimony tin oxide) films have the problem of reduced electrical performance due to oxygen adsorption on the surface and grain boundaries, and ATO can make up for the shortcomings of AZO in this regard.
[0003] AZO thin films are mostly prepared using tin antimony oxide targets or tin antimony targets, as follows:
[0004] Publication No. CN101045612A, the subject is a P-type transparent conductive tin-antimony oxide thin film material and a manufacturing method thereof, which uses molten tin-antimony to prepare a tin-antimony alloy block, and uses the tin-antimony alloy block as a target for sputtering.
[0005] Publication No. CN117105635A, the subject is a method for preparing a high-density zinc oxide-doped indium-free target material, which uses tin oxide and antimony trioxide as raw materials to prepare the tin antimony oxide target material.
[0006] According to existing literature, ATO targets have problems such as too high resistance and low density compared with ITO targets and AZO targets.
[0007] That is, ATO target material solves the defects of poor electrical performance of existing target materials, but it itself has problems such as excessively high resistance and low density.
[0008] The technical problem solved in this case is how to improve the conductivity, density and strength of ATO film. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing an ATO transparent conductive film. The method adopts an inert gas spray method to prepare a tin-antimony alloy powder and finally prepares a tin-antimony target material. The target material has the advantage of high uniformity. After being used for sputtering, the obtained film has good uniformity. The film with better uniformity can significantly improve the resistivity and density.
[0010] At the same time, the present invention also provides an ATO transparent conductive film prepared based on the method.
[0011] To achieve the above objectives, this application discloses:
[0012] A method for preparing an ATO transparent conductive film, wherein a tin-antimony target is prepared by a physical vapor deposition method to obtain the ATO transparent conductive film;
[0013] The preparation method of the tin-antimony target material comprises the following steps: mixing a molten metal liquid of a mixture of tin and antimony with an inert gas to obtain a tin-antimony alloy powder by spraying, and vacuum hot pressing the tin-antimony alloy powder to obtain the target material.
[0014] The tin antimony oxide target prepared by the traditional wet mixing method and the tin antimony target obtained by the casting method have one thing in common: poor uniformity. The problem of uniformity is mainly caused by two factors: 1. There are trace bubbles in the target; 2. The oxide or single substance mixing is not uniform enough.
[0015] In order to solve this problem, the present application adopts an inert gas spraying method. By mixing and melting first and then spraying, the metal elements are further mixed during the spraying process, and the pressure is reduced after spraying to allow the gas in the metal droplets to escape quickly, so that the metal powder does not contain impurity gases. After vacuum hot pressing, its overall uniformity is significantly improved.
[0016] The uniformity result can be indirectly reflected by the microscopic pores on the sputtered film. The ATO film prepared by the solution of the present invention has the advantages of less pores and higher density. The improvement of its density further reduces the resistivity.
[0017] In the above preparation method, the weight ratio of tin to antimony is 94.5-99.5:0.5-5.5.
[0018] In the above preparation method, the melting temperature of the molten metal is 800-900°C.
[0019] In the above-mentioned preparation method, an inert gas with a pressure of 0.5-0.8 MPa is introduced into the molten metal for a period of time to allow the molten metal to be fully mixed with the inert gas.
[0020] In the above preparation method, the consumption rate of the molten metal is 60 to 80 ml / min.
[0021] In the above preparation method, the parameters of the vacuum hot pressing are: under the condition of vacuum degree ≤10Pa, the hot pressing temperature is 150-200°C, the heating rate is 1-3°C / min, the pressure is 100-200Mpa, and the insulation and pressurizing time is 60-90min.
[0022] In the above-mentioned preparation method, the physical vapor deposition method is: using a magnetron sputtering deposition device to sputter the target material onto the substrate to obtain an ATO transparent conductive film with a film thickness of 80 to 120 nm.
[0023] In the above preparation method, during the sputtering operation, the distance between the substrate and the target material is 6 to 8 cm; protective gas is introduced during film growth, the ambient pressure is controlled at 0.4 to 0.6 Pa, the temperature is 150 to 200° C., and the deposition time is 10 to 20 min.
[0024] In the above-mentioned preparation method, the protective gas is composed of argon and oxygen, and the partial pressure of oxygen in the protective gas is 40% to 60%.
[0025] Meanwhile, the present invention also discloses an ATO transparent conductive film, which is prepared by any of the above methods.
[0026] This application has at least the following beneficial effects:
[0027] The present invention adopts an inert gas spray method to prepare tin-antimony alloy powder and finally prepare a tin-antimony target material, which has the advantage of high uniformity. After being used for sputtering, the obtained film has good uniformity. The film with better uniformity can significantly improve the resistivity and density.
[0028] The process of the present invention has the following process points:
[0029] 1. Inert gas spray method improves the uniformity of powder;
[0030] 2. Vacuum hot pressing method avoids the presence of impurity gas inside the target material;
[0031] By controlling the above two key points, a target material with high uniformity can be prepared, and the ATO film obtained after sputtering has the advantages of low resistance and high density. DETAILED DESCRIPTION
[0032] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] Example 1
[0034] (1) 49.47 kg of tin ingot with a purity of 4.5 N and 0.53 kg of antimony ingot with a purity of 4.5 N were added into an argon melting chamber with an argon pressure of 0.7 MPa and heated to 800° C. to melt the tin ingot and the antimony ingot and then fully mix them;
[0035] (2) After the molten tin-antimony liquid is fully mixed with the high-pressure argon gas, the tin-antimony liquid flows from the melting chamber to the granulation chamber at a rate of 70 ml / min and spreads in a jet-like manner. After cooling in an argon gas environment, tin-antimony alloy powder can be obtained;
[0036] (3) After the obtained tin-antimony alloy powder is loaded into a mold, it is placed in a hot pressing furnace, evacuated to 10 Pa, and then heated to 150° C. at a heating rate of 2° C. / min, and pressurized to 150 MPa. After maintaining the temperature and pressure for 70 minutes, the temperature and pressure are reduced to room temperature and pressure to obtain a tin-antimony alloy target;
[0037] (4) The tin-antimony alloy target is mounted on the target holder and then embedded in the target holder of the magnetron sputtering deposition device. The quartz substrate is cleaned and fixed on the sample stage and placed in the sputtering chamber. The distance between the substrate and the target is adjusted to 7 cm, and the substrate and the target are separated by a baffle. The vacuum degree of the growth chamber is evacuated to 3.3E-3Pa, and the substrate is heated to the film growth temperature of 150°C. Pure argon and pure oxygen are introduced, and the pressure is controlled at 0.5Pa, wherein the purity of pure argon and pure oxygen is above 99.99%, and the oxygen partial pressure is 50%. Turn on the RF power supply (sputtering power is 150w), pre-deposit for 120s to remove the contamination on the surface of the target, then unscrew the baffle and deposit the film. During the deposition process, the target rotates at a low speed to improve the uniformity of the film. The deposition time is 15min, and the film thickness is about 100nm. After the growth is completed, the film is slowly cooled to room temperature under the protection of argon to obtain an ATO transparent conductive film.
[0038] Example 2
[0039] (1) 48.94 kg of tin ingot with a purity of 4.5 N and 1.06 kg of antimony ingot with a purity of 4.5 N were added into an argon melting chamber with an argon pressure of 0.5 MPa and heated to 850° C. to melt the tin ingot and the antimony ingot and then fully mixed;
[0040] (2) After the molten tin-antimony liquid is mixed with high-pressure argon gas, the tin-antimony liquid flows from the melting chamber to the granulation chamber at a rate of 70 ml / min and spreads in a jet-like manner. After cooling in an argon gas environment, tin-antimony alloy powder can be obtained;
[0041] (3) After the obtained tin-antimony alloy powder is loaded into a mold, it is placed in a hot pressing furnace, evacuated to 10 Pa, and then heated to 180° C. at a heating rate of 2° C. / min, and pressurized to 150 MPa. After maintaining the temperature and pressure for 70 minutes, the temperature and pressure are reduced to room temperature and pressure to obtain a tin-antimony alloy target;
[0042] (4) The tin-antimony alloy target is mounted on the target holder and then embedded in the target holder of the magnetron sputtering deposition device. The quartz substrate is cleaned and fixed on the sample stage and placed in the sputtering chamber. The distance between the substrate and the target is adjusted to 7 cm, and the substrate and the target are separated by a baffle. The vacuum degree of the growth chamber is evacuated to 3.3E-3Pa, and the substrate is heated to the film growth temperature of 150°C. Pure argon and pure oxygen are introduced, and the pressure is controlled at 0.5Pa, wherein the purity of pure argon and pure oxygen is above 99.99%, and the oxygen partial pressure is 50%. Turn on the RF power supply (sputtering power is 150w), pre-deposit for 120s to remove the contamination on the surface of the target, then unscrew the baffle and deposit the film. During the deposition process, the target rotates at a low speed to improve the uniformity of the film. The deposition time is 15min, and the film thickness is about 100nm. After the growth is completed, the film is slowly cooled to room temperature under the protection of argon to obtain an ATO transparent conductive film.
[0043] Example 3
[0044] (1) 48.41 kg of tin ingot with a purity of 4.5 N and 1.59 kg of antimony ingot with a purity of 4.5 N were added into an argon melting chamber with an argon pressure of 0.8 MPa and heated to 850° C. to melt the tin ingot and the antimony ingot and then fully mixed;
[0045] (2) After the molten tin-antimony liquid is mixed with high-pressure argon gas, the tin-antimony liquid flows from the melting chamber to the granulation chamber at a rate of 70 ml / min and spreads in a jet-like manner. After cooling in an argon gas environment, tin-antimony alloy powder can be obtained;
[0046] (3) After the obtained tin-antimony alloy powder is loaded into a mold, it is placed in a hot pressing furnace, evacuated to 10 Pa, and then heated to 200° C. at a heating rate of 2° C. / min, and pressurized to 150 MPa. After maintaining the temperature and pressure for 70 minutes, the temperature and pressure are reduced to room temperature and pressure to obtain a tin-antimony alloy target;
[0047] (4) The tin-antimony alloy target is mounted on the target holder and then embedded in the target holder of the magnetron sputtering deposition device. The quartz substrate is cleaned and fixed on the sample stage and placed in the sputtering chamber. The distance between the substrate and the target is adjusted to 7 cm, and the substrate and the target are separated by a baffle. The vacuum degree of the growth chamber is evacuated to 3.3E-3Pa, and the substrate is heated to the film growth temperature of 150°C. Pure argon and pure oxygen are introduced, and the pressure is controlled at 0.5Pa, wherein the purity of pure argon and pure oxygen is above 99.99%, and the oxygen partial pressure is 50%. Turn on the RF power supply (sputtering power is 150w), pre-deposit for 120s to remove the contamination on the surface of the target, then unscrew the baffle and deposit the film. During the deposition process, the target rotates at a low speed to improve the uniformity of the film. The deposition time is 15min, and the film thickness is about 100nm. After the growth is completed, the film is slowly cooled to room temperature under the protection of argon to obtain an ATO transparent conductive film.
[0048] Comparative Example 1
[0049] (1) 49.47 kg of a tin ingot with a purity of 4.5 N and 0.53 kg of an antimony ingot with a purity of 4.5 N were mixed and melted under vacuum conditions at a melting temperature of 850° C., and then cast into a mold under vacuum conditions to obtain a casting;
[0050] (2) removing the surface layer of the casting under the protection of inert gas to obtain a tin-antimony alloy target;
[0051] (3) The tin-antimony alloy target is mounted on the target holder and then embedded in the target holder of the magnetron sputtering deposition device. The quartz substrate is cleaned and fixed on the sample stage and placed in the sputtering chamber. The distance between the substrate and the target is adjusted to 7 cm, and the substrate and the target are separated by a baffle. The vacuum degree of the growth chamber is evacuated to 3.3E-3Pa, and the substrate is heated to the film growth temperature of 150°C. Pure argon and pure oxygen are introduced, and the pressure is controlled at 0.5Pa, wherein the purity of pure argon and pure oxygen is above 99.99%, and the oxygen partial pressure is 50%. Turn on the RF power supply (sputtering power is 150w), pre-deposit for 120s to remove the contamination on the surface of the target, then unscrew the baffle and deposit the film. During the deposition process, the target rotates at a low speed to improve the uniformity of the film. The deposition time is 15min, and the film thickness is about 100nm. After the growth is completed, the film is slowly cooled to room temperature under the protection of argon to obtain an ATO transparent conductive film.
[0052] Comparative Example 2
[0053] (1) 48.94 kg of a tin ingot with a purity of 4.5 N and 1.06 kg of an antimony ingot with a purity of 4.5 N were mixed and melted under vacuum conditions at a melting temperature of 850° C., and then cast into a mold under vacuum conditions to obtain a casting;
[0054] (2) removing the surface layer of the casting under the protection of inert gas to obtain a tin-antimony alloy target;
[0055] (3) The tin-antimony alloy target is mounted on the target holder and then embedded in the target holder of the magnetron sputtering deposition device. The quartz substrate is cleaned and fixed on the sample stage and placed in the sputtering chamber. The distance between the substrate and the target is adjusted to 7 cm, and the substrate and the target are separated by a baffle. The vacuum degree of the growth chamber is evacuated to 3.3E-3Pa, and the substrate is heated to the film growth temperature of 150°C. Pure argon and pure oxygen are introduced, and the pressure is controlled at 0.5Pa, wherein the purity of pure argon and pure oxygen is above 99.99%, and the oxygen partial pressure is 50%. Turn on the RF power supply (sputtering power is 150w), pre-deposit for 120s to remove the contamination on the surface of the target, then unscrew the baffle and deposit the film. During the deposition process, the target rotates at a low speed to improve the uniformity of the film. The deposition time is 15min, and the film thickness is about 100nm. After the growth is completed, the film is slowly cooled to room temperature under the protection of argon to obtain an ATO transparent conductive film.
[0056] Comparative Example 3
[0057] (1) 48.41 kg of a tin ingot with a purity of 4.5 N and 1.59 kg of an antimony ingot with a purity of 4.5 N were mixed and melted under vacuum conditions at a melting temperature of 850° C., and then cast into a mold under vacuum conditions to obtain a casting;
[0058] (2) removing the surface layer of the casting under the protection of inert gas to obtain a tin-antimony alloy target;
[0059] (3) The tin-antimony alloy target is mounted on the target holder and then embedded in the target holder of the magnetron sputtering deposition device. The quartz substrate is cleaned and fixed on the sample stage and placed in the sputtering chamber. The distance between the substrate and the target is adjusted to 7 cm, and the substrate and the target are separated by a baffle. The vacuum degree of the growth chamber is evacuated to 3.3E-3Pa, and the substrate is heated to the film growth temperature of 150°C. Pure argon and pure oxygen are introduced, and the pressure is controlled at 0.5Pa, wherein the purity of pure argon and pure oxygen is above 99.99%, and the oxygen partial pressure is 50%. Turn on the RF power supply (sputtering power is 150w), pre-deposit for 120s to remove the contamination on the surface of the target, then unscrew the baffle and deposit the film. During the deposition process, the target rotates at a low speed to improve the uniformity of the film. The deposition time is 15min, and the film thickness is about 100nm. After the growth is completed, the film is slowly cooled to room temperature under the protection of argon to obtain an ATO transparent conductive film.
[0060] Performance Testing
[0061] The test items include the resistivity of ATO transparent conductive film and the porosity of ATO transparent conductive film;
[0062] The test method for the resistivity of ATO transparent conductive film is: four-probe method
[0063] The test method for the porosity of ATO transparent conductive film is: gas adsorption method
[0064] The test results are shown in Table 1 below;
[0065] Table 1 Test results
[0066]
[0067] Result analysis:
[0068] It can be seen from Examples 1 to 3 that after the tin-antimony alloy target prepared by the inert gas spray method is sputtered, the ATO transparent conductive film obtained has a resistivity lower than 1.8 mΩ·cm, and the number of pores larger than 100 nm (pieces / 2600 μm 2 ) is less than 15.
[0069] By comparing Example 1, Comparative Example 1, Example 2, Comparative Example 2, Example 3, Comparative Example 3, it can be found that the resistivity and porosity of the present invention are significantly lower than those of the corresponding comparative examples.
[0070] In terms of principle, we believe that by using the method of melting first and then spraying, the metal elements are further mixed during the spraying process, and the pressure is reduced after spraying to allow the gas in the metal droplets to escape quickly, so that the metal powder does not contain impurity gases. After vacuum hot pressing, its overall uniformity is significantly improved. The improvement in the uniformity of the target material directly affects the density of the ATO transparent conductive film, and the density directly affects the resistivity.
[0071] Therefore, the above experiments prove that the solution of the present invention is the most effective technical means to improve the resistivity and density (which can also be regarded as density or porosity) of the ATO transparent conductive film. The method also has the advantages of simple process and low cost.
[0072] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing an ATO transparent conductive film, characterized in that: The ATO transparent conductive film is prepared by physical vapor deposition of tin-antimony target; The preparation method of the tin-antimony target material comprises the following steps: mixing a molten metal liquid of a mixture of tin and antimony with an inert gas to obtain a tin-antimony alloy powder by spraying, and vacuum hot pressing the tin-antimony alloy powder to obtain the target material.
2. The preparation method according to claim 1, characterized in that: The weight ratio of tin to antimony is 94.5-99.5:0.5-5.
5.
3. The preparation method according to claim 2, characterized in that: The melting temperature of the molten metal is 800-900°C.
4. The preparation method according to claim 1, characterized in that: The mixing method of the molten metal and the inert gas is: the inert gas with a pressure of 0.5-0.8 MPa is introduced into the molten metal for a period of time so that the molten metal is fully mixed with the inert gas.
5. The preparation method according to claim 1, characterized in that: The consumption rate of the molten metal is 60-80 ml / min.
6. The preparation method according to claim 1, characterized in that: The parameters of the hot pressing are: under the condition of vacuum degree ≤10Pa, the hot pressing temperature is 150-200°C, the heating rate is 1-3°C / min, the pressure is 100-200Mpa, and the heat preservation and pressurization time is 60-90min.
7. The preparation method according to claim 1, characterized in that: The physical vapor deposition method is: using a magnetron sputtering deposition device to sputter a target material onto a substrate to obtain an ATO transparent conductive film with a film thickness of 80 to 120 nm.
8. The preparation method according to claim 7, characterized in that: During the sputtering operation, the distance between the substrate and the target material is 6 to 8 cm; protective gas is introduced during film growth, the ambient pressure is controlled at 0.4 to 0.6 Pa, the temperature is 150 to 200° C., and the deposition time is 10 to 20 minutes.
9. The preparation method according to claim 7, characterized in that: The shielding gas is composed of argon and oxygen, and the partial pressure of oxygen in the shielding gas is 40% to 60%.
10. An ATO transparent conductive film, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Tin antimony oxide film material of P-type transparent conduction and manufacturing method thereof
CN101045612A
Preparation method of high-density zinc oxide doped indium-free target material
CN117105635A